Application of the Software e-SAFES® (Based on SAFES Methodology) to Control Disinfection in the Sugar Extraction from Sugar Beet (Beta vulgaris L.) - Bennár, Marek; Betoret, Ester; Betoret, Noelia; Seguí, Lucía; López, Luis Mayor; Arce, David; Blanquer, Ignacio; Hernández, Vicente; Bojnanská, Tatiana; Fito, Pedro (IntechOpen, 2011)
None